2011
DOI: 10.1103/physrevb.84.174516
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle relaxation dynamics in underdoped Bi2Sr2CaCu2Oet al.

Abstract: We investigate the relaxation dynamics of photoexcited quasiparticles (QPs) in underdoped Bi 2 Sr 2 CaCu 2 O 8+δ (T c = 78 K). By changing the excitation energy and polarization of the probe beam, two different types of relaxation dynamics, associated with superconducting (SC) and pseudogap (PG) QPs, are quantitatively analyzed independently. From the temperature dependencies, we obtained the SC gap, SC (0) = 24 meV, using BCStype temperature-dependent gap and the pseudogap, PG = 41 meV. The pump fluence (F) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
64
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 38 publications
9
64
0
1
Order By: Relevance
“…For example, in the previous measurements on optimally-doped (OD) YBa 2 Cu 3 O 7-δ (YBCO) samples, the observed sign of time-resolved differential reflectivity (ΔR/R) was reported to be either positive or negative. 9,11,25,26 This fundamental discrepancy was attributed to the dependence of ΔR/R on several factors including laser power, 15,23 wavelength, 25,27 polarization, 25,28 and repetition rate 24,29 . Furthermore, in a recent effort to uncover the transient optical signatures of the pseudogap (PG) phase, [11][12][13][14]28,[30][31][32] and elucidate a possible relationship between the PG state and SC state in OD YBCO [31][32] , the PG phase was either identified as a weak transient feature 11,30 or found to be completely absent from the spectra.…”
mentioning
confidence: 99%
“…For example, in the previous measurements on optimally-doped (OD) YBa 2 Cu 3 O 7-δ (YBCO) samples, the observed sign of time-resolved differential reflectivity (ΔR/R) was reported to be either positive or negative. 9,11,25,26 This fundamental discrepancy was attributed to the dependence of ΔR/R on several factors including laser power, 15,23 wavelength, 25,27 polarization, 25,28 and repetition rate 24,29 . Furthermore, in a recent effort to uncover the transient optical signatures of the pseudogap (PG) phase, [11][12][13][14]28,[30][31][32] and elucidate a possible relationship between the PG state and SC state in OD YBCO [31][32] , the PG phase was either identified as a weak transient feature 11,30 or found to be completely absent from the spectra.…”
mentioning
confidence: 99%
“…Usually the anomalous T dependence of τ exp is observed in many gapped systems, for example, phaseordered systems showing an energy gap opening in the electron band below the transition temperature T c . It has been found that a wide variety of superconductors [1][2][3][4][5][6][7][8][9][10][11][12][13] and density-wave compounds [14][15][16][17][18][19] show diverging behavior of τ exp near T c , as confirmed by femtosecond time-resolved optical spectroscopy. 1,4,5,[7][8][9][10][11][12][13][14][15][16][17]19 The divergence of τ exp in these gapped systems is believed to result from a recursive energy transfer between electrons and phonons.…”
Section: Introductionmentioning
confidence: 91%
“…While the laser ARPES can directly resolve the momentum dependent 14 quasiparticle (QP) distribution function, all-optical techniques offer better bulk sensitivity and greater flexibility. The lack of momentum resolution of an optical probe can be partially compensated by use of the optical dipole transition selection rules that depend on the probe-photon polarization 15,16 and energy 8,17 and enable selection of different parts of the Brillouin zone (BZ).…”
Section: Introductionmentioning
confidence: 99%
“…The ultrafast S→N→S transition in the cuprate superconductors has been initially studied by all-optical [5][6][7][8][9] pump-probe technique followed by laser ARPES [10][11][12][13] . While the laser ARPES can directly resolve the momentum dependent 14 quasiparticle (QP) distribution function, all-optical techniques offer better bulk sensitivity and greater flexibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation